E COMMERCE : PASAR MAYA DI DUNIA NYATA - Lydia Mutiara Dewi (Bina Ekonomi, 2008)
Internet has been a maior tool of communication in this globalized world since these two decades. This tool can be used for many purposes so that one can fulfill interests and necessities. One purpose that arises within this virtual world is E-Commerce. lf this one implements worldwide virtual commerce correctly, E-Commerce will provide benefits for its users, E-Merchant and E-Customer. Thus, one should understand how this electronic commerce works so that one does not suffer a financial loss. E-commerce in our country is a prospective business field